The Teacher’s Emotional Culture: A Self-Education Framework for Students’ Emotional Development - Turcan, Lilia; BOROZAN, Maia (Didactica Danubiensis, 2025)
Objectives: The purpose of this research is to substantiate the significance and formative impact of the teacher's emotional culture on students’ emotional development through self-education, within the context of contemporary societal challenges. The study aims to elucidate the values embedded in the teacher's emotional culture as a model of balanced conduct and to demonstrate that self-education may serve as a meaningful contributor to the emotional development of students. Prior Work: The framework builds upon existing scholarship regarding the theoretical foundations of teacher emotional culture, the importance of developing students' emotional intelligence, and the pedagogical value of self-directed learning. Approach: Synthesizing insights from educational psychology, affective neuroscience, and contemporary pedagogy, the inquiry analyzes conceptual definitions of emotional culture, identifies core values in emotional development, examines the axiology of emotional development processes, and models the pedagogical relationship between teachers' emotional culture and students' self-directed emotional learning. Results: An evidence-based framework demonstrates how teachers' emotional culture exerts a sustained, multidimensional influence on students’ emotional development. Significant impacts are observed across three domains: enhancement of academic engagement and performance, strengthening of psychological resilience and well-being, and development of prosocial competencies. Implications: Findings are particularly relevant to educational researchers, schoolteachers, parents, students, and other stakeholders interested in emotional self-education, as they reveal the influence of the teacher’s emotional culture on students’ motivation and self-esteem. Research Value: The value lies in its axiological emphasis on the promotion of emotional culture, substantiated through references to authoritative scholars, and in its comprehensive articulation of the processual impact exerted by teachers’ emotional culture on students’ emotional development.